THE INVESTIGATION OF A BUTT WELD WITH ULTRASOUND - Claudiu BABIS; Oana CHIVU; Andrei DIMITRESCU; Loredana DASCALU; Elisabeta BANICA (Fiabilitate şi Durabilitate)
In the case of welded joints there are defects that can not be seen with the naked eye. These defects being within the material to know if they can cause failures in the future, should be investigated and ranked in an acceptance class according to certain standards in the field. In this paper we investigate using the ultrasonic control method, the welding seam between two butt welded sheets.